A Numerical Algorithm for a Kirchhoff-Type Nonlinear Static Beam - Jemal Peradze (Journal of Applied Mathematics)
A boundary value problem is posed for an integro-differential beam equation. An approximate solution is found using the Galerkin method and the Jacobi nonlinear iteration process. A theorem on the algorithm error is proved.